Multi-trait BLUP in half-sib selection of annual crops - Viana, J. M. S.; Sobreira, F. M.; Resende, M. D. V. de; Faria, V . R . (Plant Breeding, 2010)
The Best Linear Unbiased Prediction (BLUP) methodology, which is widely used in animal and forestry genetic evaluation, can also be appli ed to annual crop breeding. The objective of this study was to compare the accuracy and efficiency of among- and within-half-sib family selection through the use of single- and multi-trait BLUP, and BLUE/ ANOVA methods. Expansion volume and yield data from two recurrent selection cycles of a popcorn population were analyzed. Progeny tests were designed as a lattice. To maximize accuracy of the prediction of breeding values, the BLUP analyses included phenotypic values of the two cycles. All BLUP analyses were performed using the ASReml software. The multi-trait BLUP method demonstrated greater accuracy and efficiency in family selection. In the case of within-family selection, both accuracy and efficiency of multi- and single-trait BLUP methods were equivalent. The selection efficiency of the multi-trait BLUP was dependent on the estimated genetic parameters, particularly the difference between the genetic and environmental correlations of the traits.
Keywords: Sire model; Animal model; Genetic evaluation